NbCl5-promoted the synthesis of 4H-pyrans through multicomponent reaction - de Souza Siqueira, Mayara [UNESP]; da Silva-Filho, Luiz Carlos [UNESP] (Elsevier, 2016)
Multicomponent reactions between β-ketoesters and benzaldehydes for the synthesis of 4H-pyran derivatives promoted by niobium pentachloride (NbCl5) were carried out, providing good yields and reasonable reaction times under mild reaction conditions.
Keywords: Lewis acid; Multicomponent reaction; Niobium pentachloride; Pyran derivatives